(untitled) (Itinera, 2022)
Our paper aims at analyzing the relationship between the dimension of colour and the concept of iconic difference as it has been developed by the German philosopher Gottfried Boehm. In particular, we show how colours can contribute to the blossoming of iconic meaning in a way that cannot be fully expressed through language, thus giving access to a more authentic ontological truth of the object represented in the image. Moreover, we introduce a comparison between Boehm, Merleau-Ponty and Derrida. More specifically, we argue that Boehm’s understanding of the colour and of the concept of difference relies largely on the work of Merleau-Ponty and diverges for this reason with Derrida’s approach towards colours. Therefore, we conclude that any comparison between Boehm and Derrida should be undertaken prudently, if our goal is to appreciate the specific material features of images against the reduction of textual analysis.